Merquior, a Liberist? A Comparison of the Liberal Thought of José Guilherme Merquior and Friedrich von Hayek - Felipe, Kaio (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2015)
In this essay I seek to clarify the ideological viewpoint of José Guilherme Merquior: was he a liberist (i.e., a liberal which emphasizes the economic freedom) or a social-liberal (i.e., more concerned with civic participation and self-improvement)? In addition, I intend to analyze how Merquior stands in relation to theoretical and political formulations of Friedrich August von Hayek, considering that this is one of the liberal authors most cited and discussed in his works of the 1980s.